The Role of DNA Restriction-Modification Systems in the Biology of Bacillus anthracis - Sitaraman, Ramakrishnan (Frontiers in Microbiology, 2016)
Restriction-modification (R-M) systems are widespread among prokaryotes and, depending on their type, may be viewed as selfish genetic elements that persist as toxin-antitoxin modules or as cellular defense systems against phage infection. Studies in the last decade have made it amply clear that these two options do not exhaust the list of possible biological roles for R-M systems. Their presence in a cell may also have a bearing on other processes such as horizontal gene transfer and gene regulation. From genome sequencing and experimental data, we know that Bacillus anthracis encodes at least three methylation-dependent (typeIV) restriction endonucleases, and an orphan DNA methyltransferase. In this article, we first present an outline of our current knowledge of R-M systems in Bacillus anthracis. Based on available DNA sequence data, and on our current understanding of the functions of similar genes in other systems, we conclude with hypotheses on the possible roles of the three restriction endonucleases and the orphan DNA methyltransferase.